Subthalamic synchronized oscillatory activity correlates with motor impairment in patients with Parkinson's disease - Neumann, W; Degen, K; Schneider, G; Brücke, C; Huebl, J; Brown, P; Kühn, A (Wiley, 2016)
Beta band oscillations in the subthalamic nucleus (STN) have been proposed as a pathophysiological signature in patients with Parkinson's disease (PD). The aim of this study was to investigate the potential association between oscillatory activity in the STN and symptom severity in PD.Subthalamic local field potentials were recorded from 63 PD patients in a dopaminergic OFF state. Power-spectra were analyzed for the frequency range from 5 to 95 Hz and correlated with individual UPDRS-III motor scores in the OFF state.A correlation between total UPDRS-III scores and 8 to 35 Hz activity was revealed across all patients (ρ = 0.44, P < .0001). When correlating each frequency bin, a narrow range from 10 to 15 Hz remained significant for the correlation (false discovery rate corrected P < .05).Our results show a correlation between local STN 8 to 35 Hz power and impairment in PD, further supporting the role of subthalamic oscillatory activity as a potential biomarker for PD.